Usability Evaluation of the Alodokter Application Using the Task-Based Usability Testing Method - Achmad Dwiki Saputra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Digital health applications such as Alodokter have become essential platforms for Indonesians to access healthcare services. Although mobile health adoption continues to rise, very few studies have empirically examined how design inefficiencies affect users' ability to navigate between medical and commercial service flows, which may reduce user trust and engagement in digital healthcare platforms. Research evaluating user friction during transitions between medical flows (such as Doctor Chat) and commercial flows (such as Aloshop) within an integrated ecosystem remains limited. This study applies the Task-Based Usability Testing (TBUT) method in the Indonesian digital health context to capture fundamental user interactions beyond perception-based evaluations. The objective is to systematically evaluate the usability level of the Alodokter application by involving real users performing representative tasks across four main flows: Doctor Chat, Appointment Booking, Article Search, and Medicine Purchase through Aloshop. The evaluation employed quantitative metrics (success rate and time on task) and qualitative observation using the Think Aloud Protocol. Results show that the Appointment Booking flow had the lowest usability (success score 1.76), while the Aloshop flow was less efficient, requiring 21 seconds longer than comparable applications. The main issues identified are the lack of insurance information and inefficient cart flow. This study is limited to task-based evaluation and does not include longitudinal analysis of user behavior. These findings provide empirical foundations for data-driven design improvements to enhance user experience and advance usability evaluation methods for hybrid healthcare-commerce platforms in Indonesia. Keywords: Usability Testing, User Experience, Health Application, Alodokter, Task-Based Test